A rapidly evolving single copy histone H1 variant is associated with male fertility in a parasitoid wasp - Yuan, Bo; Yang, Yi; Yan, Zhichao; He, Chun; Sun, Yu H.; Wang, Fei; Wang, Beibei; Shi, Jiamin; Xiao, Shan; Wang, Fang; Fang, Qi; Li, Fei; et al. (Frontiers in Cell and Developmental Biology, 2023)
The linker histone H1 binds to the nucleosome core particle at the site where DNA enters and exits, and facilitates folding of the nucleosomes into a higher-order chromatin structure in eukaryotes. Additionally, some variant H1s promote specialized chromatin functions in cellular processes. Germline-specific H1 variants have been reported in some model species with diverse roles in chromatin structure changes during gametogenesis. In insects, the current understanding of germline-specific H1 variants comes mainly from the studies in Drosophila melanogaster, and the information on this set of genes in other non-model insects remains largely unknown. Here, we identify two H1 variants (PpH1V1 and PpH1V2) that are specifically predominantly expressed in the testis of the parasitoid wasp Pteromalus puparum. Evolutionary analyses suggest that these H1 variant genes evolve rapidly, and are generally maintained as a single copy in Hymenoptera. Disruption of PpH1V1 function in the late larval stage male by RNA interference experiments has no phenotype on spermatogenesis in the pupal testis, but results in abnormal chromatin structure and low sperm fertility in the adult seminal vesicle. In addition, PpH1V2 knockdown has no detectable effect on spermatogenesis or male fertility. Collectively, our discovery indicates distinct functions of male germline-enriched H1 variants between parasitoid wasp Pteromalus and Drosophila, providing new insights into the role of insect H1 variants in gametogenesis. This study also highlights the functional complexity of germline-specific H1s in animals.